A comparative analysis of the location behaviour of the global semiconductor manufacturers - Tomokazu Arita; Philip McCann (European Regional Science Association (ERSA), 2010)
In this paper, we explain the structure and technological relationships between the different sub-sectors of the global semiconductor industry, by analyzing firm-level micro data including production technological indices of wafer manufacturing processes and firm-alliances. Our results indicate that the economic geography and the location behavior of the global semiconductor industry are diverse and also fundamentally different to the types of location behavior commonly accepted in the past academic arena.
Keywords: 330